2018
DOI: 10.1515/hukin-2017-0128
|View full text |Cite
|
Sign up to set email alerts
|

Functional Movements in Japanese Mini-Basketball Players

Abstract: Functional movement screen (FMS) has been used to establish normative data and determine potential injury risk for young adults and athletes, but there are few data in elementary school-age children. The purpose of this study was to establish fundamental values for the FMS in elementary school-age mini-basketball players. Secondary purposes were to examine relationships between functional movement patterns and age, peak height velocity (PHV), and body mass index (BMI), and to compare functional movement patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…This finding is particularly noteworthy, as movement proficiency has often been theorised to improve with early aging and maturation [ 58 ]. Studies during childhood show that FMS™ scores increase with age [ 5 , 53 ]. As with sex differences, it is possible that maturation could be impacting FMS™ performance in secondary school.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is particularly noteworthy, as movement proficiency has often been theorised to improve with early aging and maturation [ 58 ]. Studies during childhood show that FMS™ scores increase with age [ 5 , 53 ]. As with sex differences, it is possible that maturation could be impacting FMS™ performance in secondary school.…”
Section: Discussionmentioning
confidence: 99%
“…Functional movement refers to movement of the body that is characterised by adequate joint and muscle function, and by a movement efficiency that has been shown to minimise the risk of injury [2,3]. Functional movement has been theorised as a precursor for higher-order, or more complex, forms of bodily movement [4], and assessments typically involve the measurement of postural control motion, stability, flexibility, neuromuscular coordination, and balance [2,3,5]. These subcomponents of functional movement have not only been recognised as enablers of high-quality bodily movement but there is also research evidence to show that these subcomponents of functional movement predict important markers of health [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The appropriate planning of a long-term training process requires the use of control tests to keep up with the evolution of athletes' morphological and physical characteristics in relation to their specific sport performance (Kuzuhara et al, 2018 ; Ryan et al, 2018 ; Myburgh et al, 2020 ). It was shown that the monitoring of players' attributes is particularly important during periods of accelerated biological development in order to control the adaption to training exposure, to reduce the injury risk, and, thereby, to enhance the coaching effectiveness process (Ryan et al, 2018 ; Salter et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A composite score is calculated as the sum of the ratings for all seven components. The Composite scores less than 14 are associated to a high risk of injury, other cutoffs have also been applied [28,29].…”
Section: Introductionmentioning
confidence: 99%